CULTURAL RESPONSIVENESS AND DIGITAL TOOLS IN LITERACY INSTRUCTION: INSIGHT FROM INDONESIAN HIGH SCHOOL TEACHERS - Vonti, Lungguh Halira; Rosyid, Abdul; Indriyani, Indriyani; Muchtar, Adam Khalsia (University of Kuningan, 2025)
Students’ literacy skill has become pivotal in the era of globalization for both academic and professional success. However, according to the observation, conventional teaching methods often fail to accommodate the cultural diversity of students and do not include essential 21st – century skills. Moreover, lesson plans that integrate 21st - century skills such as critical thinking, communication, collaboration, creativity, cultural awareness, and character development are vital for supporting students learning success. Referring to the principles of CRT and 21st century education, this research explores the English teachers’ practices and challenges in integrating culturally responsive teaching (CRT) and digital tools in literacy instructions for senior high school students. The data was collected through a structured questionnaire highlighted current practices, barriers faced, and teachers’ preferences for module design. The interview session was also conducted to confirm the data from the documentation obtained in a form of lesson plan. The findings provide valuable insights for developing teaching materials that address these challenges while fostering critical thinking, creativity, and collaboration among students. Accordingly, the data will be able to provide the possible alternatives to include in teaching module for English teachers